Struktur Anatomi Epidermis Daun Lima Kultivar Melon (Cucumis melo L.) Berdasarkan Resistensinya terhadap Jamur Tepung (Sphaerotheca fuliginea Poll) - Maryani, Maryani; Prabawani, Ratri Lila; Daryono, Budi Setiadi (Universitas Atma Jaya Yogyakarta, 2009)
Powdery mildews are plant diseases caused by fungi, including Sphaerotheca fuliginea Poll. They cause a decrease on leaves health. Plant resistance to Sphaerotheca fuliginea Poll. might have a relationship to leaf anatomical structure, especially to epidermis. Therefore, the aim of this research was to characterize epidermal leaf structure of resistant and susceptible cultivars. This study used two resistant cultivars (PI 371795 and PMAR), one susceptible cultivar (Action 434) and two other cultivars (Fresh 848 and Sakata 144) which are not known their characteristic to powdery mildews. The fifth leaves (counted from the cotyledon) were collected from melon plants which reached early generative development. Leaf epidermal slides were prepared semi permanently. The results showed that the morphological leaves of resistant cultivars have dendatus leaf edges, while the susceptible one has repandus leaf edges. Anatomically, the leaves of PI 371795 had upper epidermal cells with wavy edges, but not in the others. Both PI 371795 and PMAR 5 had irregular shape of lower epidermal cells with curved edges, while leaf epidermal cells from susceptible cultivar tended to have irregular polygonal upper and lower epidermal cells with straight edges and shorter non-glandular trichomes. PMAR 5 had long glandular trichomes. There was significant difference between cultivars in the average of stomata number, the average of stomata index and trichome number on the lower epidermal tissue, but not on the lower epidermal tissue. In the lower epidermis, PI 371 and PMAR 5 had lower average of stomata number and stomata index compared to Action 434. PMAR 5 had higher number of trichomes than susceptible cultivar (Action 434). Meanwhile, Fresh 848 cultivar tends to have similar characters to resistant ones in terms of leaf edges, lower epidermal shape, stomata number and index. Sakata 144 had similar characters to those the susceptible one in terms on leaf edges, lower epidermal cells shape, stomata number and index, but not in trichome number. It may be assumed that the first protection of melon against S. fuliginea Poll. is located on lower epidermal tissue.